Peran Pengasuh Dalam Membina Prilaku Sosial Anak Panti Asuhan - Pratama, Andy Riski; Rahmi, Annisa (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2024)
This service aims to determine the role of caregivers at the Mande Kanduang Pakan Sinayan Orphanage and foster the social behavior of foster children. The target object of this service is the head of the Mande Kanduang orphanage as well as the caretaker of the orphanage, and the children at the Mande Kanduang orphanage and their foster siblings. The results of the service show that the orphanage administrators are considered as a family for each orphanage child where the orphanage administrators and caregivers have a function as a place to fulfill love, fulfill physical needs, provide education and provide a view of life for the children as well as a place to instill values ​​and norms that apply in society. Caregivers try to act by providing rules in the orphanage to change the behavior of foster children for the better. And caregivers have an important role in fostering social behavior which is always shown by every child at the Mande Kanduang orphanage both among themselves and with the surrounding community.